Views of Critical Care Nurses Participating in an Adult Intensive Care Nursing Certification Program - ERGÜN, YASEMİN (GALENOS YAYINCILIK, 2021)
Objective: This descriptive study aimed to reveal the views of nurses who participated in an intensive care nursing certification program regarding the process of planning and implementing care. Materials and Methods: The sample comprised 218 voluntary nurses who completed an intensive care nursing certificate program in one of the four education centers. A questionnaire consisting of 25 items, of which two were open-ended questions, was used to collect data. Quantitative data were evaluated with descriptive statistics, while qualitative data obtained from the open-ended questions were examined using content analysis. Results: The average age of the participants was 31.7 +/- 7.1 years, and 81.2% were female. The majority of the participants reported satisfaction with the program content, duration, related learning methods, practical training, and educators. Moreover, the contribution level of the program to their professional knowledge and skills was 69.2 +/- 25.2%. Two main themes were determined for the content analysis of the qualitative data, namely, the design and implementation of the program and the achievements of trainees. Conclusion: Nurse participants in the intensive care nursing certificate program appeared generally satisfied with the training. However, some other arrangements are needed to design a competencybased program and to have them implemented by educators who teach using common course training materials in coordination and cooperation with all training centers.
Keywords: Certificate of need; continuing education; intensive care unit; nursing